Exposure Assessment Study on Lithium-Ion Battery Fire in Explosion Test Room in Battery Testing Facility - Mi Sung Jo; Hoi Pin Kim; Boo Wook Kim; Richard C. Pleus; Elaine M. Faustman; Il Je Yu (Elsevier, 2024)
A lithium-ion battery is a rechargeable battery that uses the reversible reduction of lithium ions to store energy and is the predominant battery type in many industrial and consumer electronics. The lithium-ion batteries are essential to ensure they operate safely. We conducted an exposure assessment five days after a fire in a battery-testing facility. We assessed some of the potentially hazardous materials after a lithium-ion battery fire. We sampled total suspended particles, hydrogen fluoride, and lithium with real-time monitoring of particulate matter (PM) 1, 2.5, and 10 micrometers (μm). The area sampling results indicated that primary potential hazardous materials such as dust, hydrogen fluoride, and lithium were below the recommended limits suggested by the Korean Ministry of Labor and the American Conference of Governmental Industrial Hygienists Threshold Limit Values. Based on our assessment, workers were allowed to return to work.